H-Hope Plus Kinesthetic With Vco On Weight And Body Length Of Preterm Infants - Lia Dian Ayuningrum (Alma Ata University Press, 2019)
Prematurity is still a major health problem worldwide. Premature babies with LBW are at risk of developing growth disorders, especially body weight. Prematurity complications in the first year contribute to one million children die and each year around 15 million babies are born prematurely. One intervention that can be given is visual-tactile-kinesthetic stimulation. This stimulation is a stimulus series that provides sensory and motor experiences so that premature babies can show their appropriate growth progress. This research to determine the effectiveness of H-HOPE plus kinesthetic with VCO on the weight and body length of preterm infants. This type of experimental design study with pretest-posttest with control group design with independent variables was intervention in the form of H-HOPE plus Kinesthetic with VCO and Kangaroo Mother Care (KMC). The samples in this study were preterm infants post Hospital-Care. Sampling used probability sampling technique with random sampling. The number of samples in this study is 30 respondents with 15 people in the intervention and control groups. The results of giving H-Hope plus kinesthetic with VCO interventions for 14 days in increasing weight and body length obtained sig value of 0.001 and 0.009 H-Hope plus kinesthetic with VCO is more effective in increasing weight and body length.